子宮内高血糖における骨格筋分化に対する脂肪酸の影響 - 德永, 弥月; 河原田, 律子; 石田, 千聡; 中村, 彰男 (日本薬理学会年会要旨集, 2020)
INTRODUCTION: The effect of unsaturated fatty acids on skeletal muscle differentiation in an intrauterine hyperglycemic environment has not been clarified. We explored the effect of maternal nutrition on myotubes formation using the L6 rat myoblast cell model exhibiting hyperglycemia during pregnancy.METHODS: Rat L6 skeletal myoblasts were grown in DMEM medium containing 100 mg/dL glucose (control), and subsequently it examined the effect of palmitate against the differentiation into myotubes in differentiation medium containing control or 450 mg/L (high glucose). Phospho-Akt was detected by western blotting and the expressions of muscle differentiation markers (myf5 and myoD) were evaluated by real-time PCR.RESULTS: The gene expression of myf5 and myoD and the level of the Phospho-Akt were significantly higher in high glucose than in control with myogenic differentiation. Palmitate decreased the expression level of myf5 and myoD in 24 hours, however, their expression level increased again after 48 hours. Palmitate also was decreased the Phospho-Akt with differentiation.CONCLUSION: We showed that palmitate suppressed myogenic differentiation in hyperglycemic condition. We would like to explore the influence of other unsaturated fatty acid against myogenic differentiation.